Mange striber på kryds og tværs - Seeberg & H. Kristensen, Peter & H. (Kuml, 1964)
Many criss-cross furrows Viborg Museum has, in the past three years, investigated three tumuli of neolithic date, all covering a network of ard furrows. At Aptrup a tumulus, ploughed down to a maximum height of 75 cms, with a diameter of about 13 meters and apparently no ring stones, covered a plank-coffin burial, the lowest plank of which rested on the subsoil (Fig. 3). The burial contained a battleaxe, while a secondary, stone-framed burial at the west edge of the tumulus and ten cms. above subsoil contained a little cord-ware beaker (Fig. 4). The ard furrows covered an irregular area reaching to within 1.5 meters of the edge of the tumulus. The furrows lay in two directions, E-W and NNW-SSE, the former being clearer, and were about 30 cms. apart and 5-15 cms. broad. The hard clay retained the impress of the U-shaped, sometimes slightly oblique, furrow to a depth of 2-8 cms. The furrows cross the top of -and are therefore later than- a pit containing charcoal dated by C-14 analysis to 2740 ± 100 BC (K 955), while they are earlier than the grave furnishings, which both belong to the transitional period between the bottom-grave and ground-grave subdivisions 1). At Lerchenfeldt a mound, with a diameter of 13.5 meters and preserved to a height of 1.5 meters, contained a trough-shaped stone bedding suggesting a perished oak-coffin burial, secondary urn and cremation burials of Late Bronze Age date, and portions of a ring of quite large edge stones. The mound, of turves, had been laid above the original topsoil, and the net of ard furrows covered the whole area under the mound and the ring-stones, being visible in the subsoil sand and in one area even traceable up through the topsoil (Fig. 4), showing the depth of ploughing to have been at least 20-25 cms. (allowing for compression of the topsoil). Furrows lay in two directions, E-W and NNW-SSE (Fig. 5), the E-W furrows being only half the distance apart of the others, 10-15 cms. against about 30 cms. The width of the actual furrows was 2-15 cms., and in section they were symmetrically semicircular. Two fragments of cord-decorated ware from the furrows give a lower limit for their dating, and the central grave an upper limit. At South Borup a ruined tumulus, about 15 meters in diameter, had had its primary grave removed, but contained peripheral secondary burials, including one ground-grave. In the subsoil sand a small area showed a net of ard furrows, in two directions with an interval of 25 cms. between the furrows, themselves about 5 cms. wide (Fig. 6). Five sherds of neolithic type, one reminiscent of the single-grave and another of the funnel-beaker cultures, were found at subsoil level in and near the furrow area. These three excavations show ploughing taking place in stiff clay, sand and humus/sand. The instrument used could clearly work heavy soil and plough to a depth of 20-25 cms. The presence of furrows below three tumuli associated with the single-grave culture brings into question the traditional belief that the single-grave people had an ecology based entirely upon cattle-raising 5), and that furrows beneath their tumuli should be attributed to earlier inhabitants of the same area 3). This theory can perhaps be tested by experiments to find out how long furrows persist in the subsoil when not covered by a tumulus. The fact that the furrows under the Aptrup tumulus disappear towards the edge of the mound, where the coating of soil is thinnest, suggests that traces of furrows may have a limited "life" under open field conditions. Peter Seeberg and H. H. Kristensen